Pencegahan Stunting sebagai Investasi Ekonomi Desa melalui Edukasi dan Optimalisasi Dana Desa - Masitah Masitah; Jauharil Maknuni; Rona Elia (BA: Jurnal Pengabdian kepada Masyarakat, 2025)
Stunting is a chronic health problem that affects the quality of human resources and long-term economic development, particularly in rural areas. Stunting prevention requires a comprehensive approach that integrates health interventions with village economic instruments, especially the Village Fund. This community service program aims to enhance the awareness and commitment of communities and village authorities in preventing stunting through education and optimization of the Village Fund. A participatory and collaborative approach was applied through socialization activities, focus group discussions, and mentoring for village officials, village councils, health cadres, and target communities, particularly pregnant women, prospective brides, and families with children aged 0–24 months. The results indicate improved awareness among communities and village stakeholders regarding stunting as an investment in village economic development, strengthened commitment to allocating Village Fund resources for health-related programs, and the establishment of cross-sector collaboration involving village governments, health centers, and higher education institutions. The program generated initial impacts in increasing community understanding of nutrition, sanitation, and clean and healthy living behaviors as integral components of stunting prevention. Therefore, village-based economic education and Village Fund optimization represent a strategic approach to supporting sustainable stunting reduction efforts.